The relationship between burnout and substance use in collegiate athletic trainers - Oglesby, L. W.; Gallucci, A. R.; Wynveen, C. J.; Ylitalo, K. R. (Journal of Athletic Training, 2019)
Context: Burnout is a psychological syndrome that includes emotional exhaustion, a decreased perception of personal accomplishment, and depersonalization. Among healthcare professionals, burnout and substance abuse are well-documented. For example, increases in self-reported burnout symptoms are associated with increases in heavy episodic drinking among physicians, medical students and psychiatrists. Similarly, increases in tobacco use have also been associated with high levels of burnout among nurses. Smith's Cognitive-Affective Model of Athletic Burnout suggests that athletic trainers (ATs) suffering from burnout may engage in substance use as a coping behavior; however, this relationship has not been examined thoroughly. The purpose of this study was to examine burnout and its relationship with substance use in collegiate athletic trainers. Methods: A web-based, cross-sectional study design via the National Athletic Trainers' Association (NATA) membership directory email broadcast service was utilized to sample ATs working full time in the college/university setting. Graduate assistants, interns, and other parttime employees were excluded. Participants (n=783; 57.9% female) were 36.4 ± 11.1 years old (range 22-79 years). The questionnaire consisted of survey items from previously used scales, including the Maslach Burnout Inventory (MBI) and substance use questions from the Monitoring the Future study. The survey took approximately 15 minutes to complete. Path analyses were used to analyze survey data. All independent (MBI subscales) and dependent variables (e.g. alcohol consumption, tobacco use and marijuana use) were mapped onto Smith's Cognitive-Affective Model of Athletic Burnout to determine which dimensions of burnout alter the odds of self-reported substance use. Results: Almost half (46.3%) of the participants indicated that they had engaged in at least one episode of heavy episodic drinking (5 or more drinks in a row for males, 4 or more for females) in the previous month and nearly one quarter (22.9%) consumed at least one energy drink in the same time frame. However, the use of cigarettes (1.4%), smokeless tobacco (5.2%), and marijuana (3.5%) during the last month was less common in the sample. Emotional exhaustion (B = .008, p = .023; 95% CI = 0.001, 0.015) and decreased personal accomplishment (B = -.016, p = .02; 95% CI = -0.029, -0.003) were associated with binge drinking. Emotional exhaustion (Exp[B] = 1.017, p < .001; 95% CI = 1.009, 1.026) was also positively correlated with energy drink consumption. Conclusions: Many collegiate ATs engage in heavy episodic drinking. Subscales of burnout (i.e. emotional exhaustion and a decreased sense of personal accomplishment) are significantly correlated with this behavior. Emotional exhaustion is also positively correlated with energy drink use in collegiate ATs. Because substance use/abuse may affect work performance and therefore affect patient outcomes, further examination of these relationships in collegiate ATs as well as ATs in other work settings is warranted.